2017
DOI: 10.1038/s41598-017-13953-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of laser surface remelting on the microstructure and properties of Al-Al2Cu-Si ternary eutectic alloy

Abstract: Bimodal ultrafine eutectic composites (BUECs) exhibit a good combination of strength and plasticity owing to a dual-hierarchy in eutectic length-scales in the microstructure. The present study investigates the variation of phase, morphology, feature length-scales and modality of microstructures obtained in a Al81Cu13Si6 (at. %) ternary alloy after laser surface remelting. A novel approach of varying component bimodal eutectic volume fractions by controlling the cooling rate of the laser solidification process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…(denoted by blue arrows) are randomly distributed in a nanoscale eutectic structures (denoted by yellow arrows). As reported in previous studies [16,20,21], the cellular structures are identified as binary eutectic of α-Al and θ-Al 2 Cu, the ultrafine ternary eutectic matrix is consisted of the α-Al, θ-Al 2 Cu and β-Si. Figure 1(c) reveals an obviously hypoeutectic structure of Al 88 Cu 8 Si 4 alloy.…”
Section: Methodssupporting
confidence: 63%
“…(denoted by blue arrows) are randomly distributed in a nanoscale eutectic structures (denoted by yellow arrows). As reported in previous studies [16,20,21], the cellular structures are identified as binary eutectic of α-Al and θ-Al 2 Cu, the ultrafine ternary eutectic matrix is consisted of the α-Al, θ-Al 2 Cu and β-Si. Figure 1(c) reveals an obviously hypoeutectic structure of Al 88 Cu 8 Si 4 alloy.…”
Section: Methodssupporting
confidence: 63%
“…To block the high localized shear deformation, some inhomogeneous microstructures such as the micron-scale soft and ductile dendritic phase have been introduced into the nano/ultrafine matrix [11][12][13][14][15][16][17][18][19]. Although these nano/ultrafine structured composites exhibited an excellent compressive plasticity, they still exhibited very limited macroscopic plasticity under tensile stress.…”
Section: Introductionmentioning
confidence: 99%
“…Laser-based processing, such as direct metal deposition and other related approaches, has significant potential in the synthesis of designed metallic nanocomposites of the future. 49,50 Likewise, 3D printing 51 has shown promise through high spatial fidelity, flexibility, and high throughput to process large-scale bioinspired architectured materials with improved mechanical properties.…”
Section: Resultsmentioning
confidence: 99%